70% ethanol preserves mycobacterial RNA from cultures more efficiently than GTC-TCEP - Lena Krausser; Magalie Van Dyck-Lippens; Ramata Balde; Rabab Reenaers; Reem Al Mubarak; Leen Rigouts; Nicholas D. Walter; Martin I. Voskuil; Annelies Van Rie; Bouke C. de Jong; Sofie M. Braet (Scientific Reports)
Abstract RNA-based assays hold great potential for assessing viability molecularly in slow- or non-growing mycobacteria, and RNAseq has evolved into a powerful tool in infectious disease research. Such applications require efficient RNA preservation for optimal results. The performance of 70% ethanol as simpler alternative to commonly-used GTC-based storage of mycobacteria at − 80 °C was compared on cultured Mycobacterium tuberculosis H37Ra subjected to following setups: a 45 °C heat shock to test immediate stabilisation, five freeze-thaw scenarios to mimic different shipping conditions, and long-term storage at -80 °C, -20 °C, 4 °C or 30 °C for up to twelve months. Treatment with 70% ethanol yielded overall higher RNA quantities compared to GTC-TCEP and RNA integrity was maintained at -20 °C for twelve months. Both buffers are reportedly mycobactericidal and, in this study, prevented heat stress-induced transcriptomic changes, thereby conserving a transcriptomic snapshot. RNA yield and integrity remained unaltered after treatment with 70% ethanol, even with up to three freeze-thaw cycles. Based on these results, we recommend 70% ethanol over GTC-TCEP for RNA preservation of mycobacterial cultures. While freeze-thawing, short-term high-temperature and − 20 °C long-term storage results are promising, this inexpensive, widely available buffer needs further validation prior to applying it for RNA-based analysis in clinical samples.